2012
DOI: 10.3109/15622975.2012.669047
|View full text |Cite
|
Sign up to set email alerts
|

A placebo-controlled, double-blind study of the efficacy and safety of aripiprazole for the treatment of acute manic or mixed episodes in Asian patients with bipolar I disorder (the AMAZE study)

Abstract: Aripiprazole had significantly greater efficacy than placebo for the treatment of acute manic or mixed episodes associated with bipolar I disorder in Asian patients. Treatment was generally safe and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…There are 5 positive (Keck et al, 2003b, 2009; Sachs et al, 2006; Young et al, 2009; Kanba et al, 2014) and one negative fixed dosage study (El Mallakh et al, 2010) concerning the efficacy of aripiprazole 15 to 30 mg/d for the treatment of acute manic and mixed episodes. One study was not completed and reported no results.…”
Section: Efficacy Datamentioning
confidence: 99%
“…There are 5 positive (Keck et al, 2003b, 2009; Sachs et al, 2006; Young et al, 2009; Kanba et al, 2014) and one negative fixed dosage study (El Mallakh et al, 2010) concerning the efficacy of aripiprazole 15 to 30 mg/d for the treatment of acute manic and mixed episodes. One study was not completed and reported no results.…”
Section: Efficacy Datamentioning
confidence: 99%
“…One article (Keck et al, 2009) compared aripiprazole monotherapy and lithium in the acute phase of illness (aripiprazole = 155; lithium = 160), another article (El-Mallakh et al, 2012) compared aripiprazole monotherapy versus lithium in the maintenance stage (aripiprazole = 25; lithium = 38), and another article (Jeong et al, 2012) investigated the combination of aripiprazole with valproic acid versus haloperidol with valproic acid (aripiprazole = 28; haloperidol = 14). The remaining 15 articles (Carlson et al, 2012;El Mallakh et al, 2010;Findling et al, 2013;Findling et al, 2009;Findling et al, 2012;Kanba et al, 2014;Keck et al, 2007;Keck et al, 2003;Muzina et al, 2008;Quante et al, 2010;Sachs et al, 2006;Thase et al, 2008;Tramontina et al, 2009; A C C E P T E D M A N U S C R I P T …”
Section: Study Selectionmentioning
confidence: 99%
“…Therefore, 20 articles were eligible for the current meta-analysis (Carlson et al, 2012;El-Mallakh et al, 2012;El Mallakh et al, 2010;Findling et al, 2013;Findling et al, 2009;Findling et al, 2012;Jeong et al, 2012;Kanba et al, 2014;Keck et al, 2007;Keck et al, 2003;Keck et al, 2009;Muzina et al, 2008;Quante et al, 2010;Sachs et al, 2006;Thase et al, 2008;Tramontina et al, 2009;Vieta et al, 2005;Vieta et al, 2008;Woo et al, 2011;Young et al, 2009) (Table 1). …”
Section: Study Selectionmentioning
confidence: 99%
“…Both the FDA guidelines and those of the EMA allow the use of the drug in these conditions from 15 to 30 mg/day, but they recommend doses of 15 mg. The only study that used a fixed dose of 15 mg of ARI [23] showed no efficacy compared to PCB. Thus clinicians must consider the possibility of using ARI at a high dose in the allowed range but also that the risk of EPS is dose-dependent [55].…”
Section: Expert Opinionmentioning
confidence: 83%
“…5.1 Treatment of acute manic or mixed episodes We found six RCTs versus placebo (PCB) on efficacy of oral ARI in the treatment of acute mania and mixed states in adults with BD type-1 (DSM-IV) [23][24][25][26][27][28]. These trials have in common the inclusion of people with ‡ 18 years old, the duration of 3 weeks and the primary outcome (mean change in the Young Mania Rating Scale [YMRS] at the end measured with the Last Observation Carried Forward [LOCF] dataset).…”
Section: Clinical Efficacy and Safetymentioning
confidence: 99%